Grassmann dynamics of classical spin in nonabelian gauge fields - Pol’shin, S.A. (Вопросы атомной науки и техники, 2012)
Using Grassmann variant of classical mechanics, we construct Lagrangian dynamics of classical spinning particle in (possibly non-abelian) gauge fields. Quantization of this model is briefly discussed.